The efficacy and safety of modified bortezomib‐lenalidomide‐dexamethasone in transplant‐eligible patients with newly diagnosed multiple myeloma. (28th November 2019) - Okazuka, Kiyoshi; Ishida, Tadao; Nashimoto, Junichiro; Uto, Yui; Sato, Kota; Miyazaki, Kanji; Ogura, Mizuki; Yoshiki, Yumiko; Abe, Yu; Tsukada, Nobuhiro; Suzuki, Kenshi
Abstract: Objectives: Bortezomib with lenalidomide and dexamethasone (VRd) is a standard induction regimen for transplant‐eligible patients with newly diagnosed multiple myeloma (NDMM). However, some patients discontinue VRd because of severe adverse events, despite its high efficacy. We aimed to study the efficacy of modified dose of VRd (VRd lite) in transplant‐eligible patients with NDMM. Methods: Forty‐eight transplant‐eligible patients with NDMM were included. VRd lite was administered every 4 weeks. Bortezomib 1.3 mg/m 2 was administered subcutaneously on days 1, 8, 15 and 22, and dexamethasone 20 mg was administered orally on the day of and the day after bortezomib administration. Lenalidomide was omitted on days 1, 8 and 15, which are the days of bortezomib administration. Results: The overall response rate (ORR) after four cycles of VRd lite was 83%, including a complete response of 25%. Thirty‐eight among the 45 patients who completed at least four cycles of VRd lite received autologous stem cell transplantation (ASCT). The ORR and very good partial response or better were upgraded to 100% and 74%, respectively, following ASCT. Conclusion: Our strategy consisting of VRd lite followed by ASCT is, thus, a highly effective and well‐tolerated regimen resulting in durable responses in patients with NDMM.